Microalgal Bioprocess Toward the Production of Microalgal Oil Loaded Bovine Serum Albumin Nanoparticles - Inan, Benan; Ozcimen, Didem (SPRINGER, 2021)
Microalgal biotechnology has increased rapidly owing to have high value bioactive compounds and numerous consumer products that can be utilized from microalgae. With the development of novel cultivation and processing methods, microalgal biotechnology can meet the high demands of food, energy and pharmaceutical industries. In this context, especially for food and pharmaceutical applications, encapsulation of microalgal bioactive compounds is carried out to protect the compound from oxidation and degradation. In this study, a microalgal production process was carried out and microalgal oil loaded bovine serum albumin (BSA) nanoparticle production using glucose as cross-linking agent was investigated. The influences of different process parameters such as initial BSA concentration, glucose concentration and desolvation temperature on the size of BSA nanoparticles were investigated to achieve very small size nanoparticles. Furthermore, data obtained from the experiments were assessed statistically to model the process. It was found that the obtained nanoparticles showed spherical shape with the mean particle size of around 200-300 nm with zeta potential of about - 23 mV. Also, stability test showed that, there was not any change in particle size for one month storage and nanoparticle structure enhance the protection of microalgae oil from oxidation. At last, antibacterial effect of nanoparticles was presented against E. coli ATCC 8739 and L. monocytogenes ATCC 13932. In here, we demonstrated a microalgal bioprocess which consists of microalgae production to obtain microalgal oil riched in bioactive and, encapsulation of microalgal oil to protect it from environmental conditions.
Keywords: BSA nanoparticles; Microalgae; Encapsulation; Antibacterial activity; Bioactives; Biochemistry & Molecular Biology